Efficient, but Ethical? A Qualitative Study on AI-supported Recruitment - Grundström,Hannah; Högberg,Elsa; Kahrimanovic,Ines (2026)
The use of AI-supported recruitment systems is increasing rapidly, raising important ethical questions. The study explores how HR professionals perceive and manage ethical challenges related to AI-supported recruitment, as well as how these challenges are managed in practice. The study is based on a qualitative method where semi-structured interviews were conducted with six respondents working with AI-supported recruitment in Sweden and the United States. The analysis is grounded in a theoretical framework and previous research concerning algorithmic bias, fairness, transparency, human oversight, and AI regulation. The findings indicate that AI is often perceived as a valuable support tool that may contribute to more structured and consistent recruitment processes while reducing certain forms of subjective human bias. At the same time, respondents express concerns regarding algorithmic bias, lack of transparency, overreliance on automated systems and uncertainty regarding the interpretation of legal and regulatory requirements. The study further shows that human involvement, education, and critical evaluation of AI-generated outputs are perceived as central strategies for mitigating ethical risks. Overall, the findings suggest that ethical AI use in recruitment is shaped through the interaction between technological systems, human judgment, organizational practices, and the interpretation of legal and regulatory frameworks.
Keywords: AI ethics; algorithmic decision making; human judgement; recruitment; HR-professionals